2009
DOI: 10.1111/j.1445-5994.2008.01721.x
|View full text |Cite
|
Sign up to set email alerts
|

Hip fracture in Auckland: contrasting models of care in two major hospitals

Abstract: The orthogeriatric model of care at NSH was associated with a shorter overall length of stay, earlier transfer to the Assessment, Treatment and Rehabilitation setting, and a higher proportion rehabilitated in Assessment, Treatment and Rehabilitation. Outcomes in terms of discharge destination and 6-month mortality were similar at both centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…30 At the hospital level, an orthogeriatric service in New Zealand reduced hospital stay and increased the rate and promptness of transfers to rehabilitation, without altering 6-month mortality. 17 The 12-month mortality for community-dwelling patients was not associated with length of hospital stay in an orthogeriatric unit in Oslo. 31 An Australian study over a 10-year period showed reductions in 30-day mortality from 12.1% to 8.2%, whereas LOS increased marginally.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…30 At the hospital level, an orthogeriatric service in New Zealand reduced hospital stay and increased the rate and promptness of transfers to rehabilitation, without altering 6-month mortality. 17 The 12-month mortality for community-dwelling patients was not associated with length of hospital stay in an orthogeriatric unit in Oslo. 31 An Australian study over a 10-year period showed reductions in 30-day mortality from 12.1% to 8.2%, whereas LOS increased marginally.…”
Section: Discussionmentioning
confidence: 94%
“…[14][15][16] However, evidence for an association between orthogeriatric acute care and longerterm benefits is inconsistent. 12,17,18 The acute phase of care is coming under particularly close scrutiny in national audit programs that document compliance with recommended process elements and report comparative rates of short-term outcomes. Performances are compared between health services or, more commonly, between individual hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…This time to surgery is similar to previously published data for Christchurch 11 (43.5 hours) and Middlemore Hospital (44 hours). 12 Northshore Hospital has significantly shorter times to surgery (21 hours), with 58% having surgery within 24 hours, which may be due to performing surgery after hours for neck of femur fractures. 12 The percentage of patients having surgery within 24 hours in Dunedin (27%) is similar to Middlemore (26%) and Auckland (24%).…”
Section: Discussionmentioning
confidence: 98%
“…12 Northshore Hospital has significantly shorter times to surgery (21 hours), with 58% having surgery within 24 hours, which may be due to performing surgery after hours for neck of femur fractures. 12 The percentage of patients having surgery within 24 hours in Dunedin (27%) is similar to Middlemore (26%) and Auckland (24%). 13 The main reason for delay in medically well patients was theatre unavailability.…”
Section: Discussionmentioning
confidence: 98%
“…However, contemporary Australian evidence suggests that an orthogeriatric model of care reduces length of stay (LOS) and can lead to a 45% decrease in the probability of complications such as delirium, congestive cardiac failure (CCF), pneumonia, deep vein thrombosis (DVT), pulmonary embolism (PE), pressure ulcers, arrhythmias, myocardial infarction and mortality. Conversely, Tha et al (2009) argue that the best design and setting of comprehensive hip fracture management in the elderly is unknown. Regardless, the mainstay of treatment is surgical repair and a multidisciplinary, co-managed approach that may maximise patient recovery (Hung, Egol, Zuckerman, & Si, 2012).…”
Section: Introductionmentioning
confidence: 99%